Factors of Ontological Security and their Impact on Foreign Policy of Serbia and Türkiye - Dmitry V. Efremenko; Daniil O. Rastegaev (Современная Европа)
The article deals with the problem of ontological security of Türkiye and Serbia and its impact on the foreign policy of these states. The different historical paths of these states inevitably leave their imprint on the macro-political communities' vision of their history and, accordingly, on the arrangement of foreign policy priorities. In Türkiye, “neo-Ottomanism” and the desire to regain leadership in the Islamic world are at odds with the ideological and institutional legacy of Mustafa Kemal Ataturk, the founder of the Republic. Serbia, which current statehood is based on the foundations laid by Slobodan Milosevic, is forced to adapt the “Kosovo” founding myth to the contemporary geopolitical realities of the Southwest Balkans; the victim and defensive narratives construed to reduce ontological insecurity are already struggling to do so.